Foucault, najpierw, służy czynieniu wojny - Solarska, Maria (Er(r)go. Teoria - Literatura - Kultura, 2001)
Maria Solarska Foucault, First of All, Serves the Making of War Maria Solarska undertakes an examination of selected aspects of Foucault's vision of history. First of all, she observes that Foucault's writing is characterised by spatial metaphors. His historiography is a description of certain spatial configurations and thus can be inscribed within the contemporary tendencies in historiography which replace the linear notion of time with multiplied duration (duree). Foucault's project requires that he should use geographical terms of description, spatial tropes and architectural figures. Those include his notions of utopia and heterotopia, which Solarska discusses at length in the latter part of her essay pointing to the belligerent overtones of Foucault's statements.